A mini-review on co-supplementation of probiotics and medicinal herbs: Application in aquaculture - Wei, Lee Seong; Goh, Khang Wen; Abdul Hamid, Noor Khalidah; Abdul Kari, Zulhisyam; Wee, Wendy; Van Doan, Hien (Frontiers in Veterinary Science, 2022)
The aquaculture industry is geared towards intensification and successfully meets half of the world's demand for fish protein. The intensive farming system exposes the animal to the risk of disease outbreaks, which has economic consequences. Antibiotics are commonly used for the health management of aquaculture species. However, this has several drawbacks, including the increase in antibiotic resistance in pathogenic bacteria and the entry of antibiotic residues into the human food chain, a public health and environmental concern. The potential of probiotics, prebiotics, synbiotics, and medicinal herbs as alternatives to antibiotics for the health management of aquaculture species has been investigated in numerous studies. This review discusses the potential use of combinations of probiotics and medicinal herbs as prophylactic agents in aquaculture, along with the definitions, sources, and modes of action. The positive aspects of combining probiotics and medicinal herbs on growth performance, the immune system, and disease resistance of aquaculture species are also highlighted. Overall, this review addresses the potential of combinations of probiotics and medicinal herbs as feed additives for aquaculture species and the key role of these feed additives in improving the welfare of aquaculture species.